Psychological empowerment, job satisfaction, and employees commitment of hotel employees in Krabi - Narongchai U-Yhanang (มหาวิทยาลัยสงขลานครินทร์, 2016)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2012